Memory, territory and pottery trade Collective memory in Cerro del Cable hillside neighborhoods: La memoria colectiva en los barrios del Cerro del Cable (2011)
The article attempts to establish the principal characteristics of the inhabitant’s collective memory in Cerro del Cable hillside neighborhoods (Bogota), focusing on the relationship between collective memory and the construction of a neighborhood identity, based on territory appropriation and the sharing of pottery as a common trade. From this perspective, the article touches upon issues like the first hillside settlements, the following construction of neighborhoods, the collective efforts to improve common areas and services, the introduction of the community to pottery industry, the different stages for brick production and the working conditions at pottery factories and brickyards.